1994
DOI: 10.1139/v94-028
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of naphthomycin A in Streptomyces collinus

Abstract: The biosynthesis of naphthomycin A (1) in Streptonzyces collirt~rs was studied in feeding experiments with single and multiple I3c-labeled precursors followed by I3c NMR analysis of the labeling and I3c-l3c coupling patterns in the product. The results indicate that 1 is assembled via the polyketide pathway from 3-amino-5-hydroxybenzoic acid (2) as the starter unit (mC7N unit) plus seven propionate and six acetate chain extension units. 2 is synthesized via the shikimate pathway by a process that attaches the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Later work has repeatedly confirmed the specific role of AHBA as precursor of the mC 7 N unit of various other compounds. [34][35][36][37][38][39] The biosynthetic question then raised was how AHBA was formed by a route that is related to the shikimate pathway. An important issue was whether the nitrogen of AHBA was attached to the carbon corresponding to C-3 or C-5 of shikimate.…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Later work has repeatedly confirmed the specific role of AHBA as precursor of the mC 7 N unit of various other compounds. [34][35][36][37][38][39] The biosynthetic question then raised was how AHBA was formed by a route that is related to the shikimate pathway. An important issue was whether the nitrogen of AHBA was attached to the carbon corresponding to C-3 or C-5 of shikimate.…”
Section: Historymentioning
confidence: 99%
“…Subsequent work in other systems also confirmed the site of attachment of the nitrogen. 26,37 On the basis of the mitomycin work, Hornemann et al 21 proposed 3,4-dideoxy-4-amino-D-arabino-seduheptulosonic acid 7-phosphate (amino-DAHP), which he hypothesized to arise from DAHP, as the specific precursor of the mC 7 N unit. We subsequently modified this hypothesis based on a report by the group of Jiao 41 that the nitrogen of rifamycin is derived from the amide nitrogen of glutamine.…”
Section: Historymentioning
confidence: 99%
“…Continuing these studies, effort has been made to identify the point of divergence from the common shikimate pathway.ls6 An early demonstrated intermediate is the dihydroxydiene (1 86), but this might arise in several ways, namely, dehydration of shikimate, loss of phosphoric acid from shikimate 3-phosphate, or loss of pyruvate from chorismate (Scheme 52). Labelled [2,6,10, 10-2H,]chorismate was fed to Streptornyces collinus, a producer of ansatrienin A (188), and to Alicyclobacillus acidocaldarius, which synthesizes w-cyclohexylundecanoic acid (189). Since labelled shikimic acid is known to be transformed into labelled cyclohexanecarboxylic acid as shown in Scheme 53 (see Ref.…”
Section: Ephedra Alkaloidsmentioning
confidence: 99%
“…1) [1]. Feeding experiments with rifamycin (produced by Amycolatopsis mediterranei ), ansatrienin [2] and naphthomycin [3] (produced by Streptomyces collinus ) have demonstrated that the polyketide chain of these antibiotics is assembled from acetate and propionate units in a manner typical of that catalyzed by a multifunctional type I polyketide synthase [4]. The starter unit for these antibiotics is 3‐amino‐5‐hydroxybenzoic acid (AHBA) derived by the newly discovered aminoshikimate pathway, a process which parallels the initial steps of the shikimate pathway (Fig.…”
mentioning
confidence: 99%